2022
DOI: 10.3390/ph15020239
|View full text |Cite
|
Sign up to set email alerts
|

Black Elder and Its Constituents: Molecular Mechanisms of Action Associated with Female Reproduction

Abstract: The present review summarizes the current knowledge concerning provenance, properties, physiological and therapeutic actions of elderberry and the bioactive molecules present in the plant, with emphasis on their action on female reproduction. Elderberry or black elder (Sambucus nigra L.) attracts attention due to its easy cultivation and high availability of bioactive compounds. Most of the available data concerning black elder’s therapeutic action are focused on its effects such as activation of immune proces… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 105 publications
(212 reference statements)
0
5
0
Order By: Relevance
“…44 Previous studies have shown that anthocyanins could enhance the viability and steroidogenesis of healthy ovarian cells, as well as promote apoptosis and decrease the viability and proliferation of OC cells. 51–53 In addition, as a critical carotenoid pigment in red/purple FV, lycopene could interfere with mechanisms involved in the development and progression of OC, and reduced the tumor and metastatic burden of OC. 54,55…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…44 Previous studies have shown that anthocyanins could enhance the viability and steroidogenesis of healthy ovarian cells, as well as promote apoptosis and decrease the viability and proliferation of OC cells. 51–53 In addition, as a critical carotenoid pigment in red/purple FV, lycopene could interfere with mechanisms involved in the development and progression of OC, and reduced the tumor and metastatic burden of OC. 54,55…”
Section: Discussionmentioning
confidence: 99%
“…44 Previous studies have shown that anthocyanins could enhance the viability and steroidogenesis of healthy ovarian cells, as well as promote apoptosis and decrease the viability and proliferation of OC cells. [51][52][53] In addition, as a critical carotenoid pigment in red/purple FV, lycopene could interfere with mechanisms involved in the development and progression of OC, and reduced the tumor and metastatic burden of OC. 54,55 Notably, a diet is made up of multiple food groups and nutrients, so recommendations for a high pre-diagnosis FV intake also need to consider the intake of other food groups , total fruits is 158.00 g day −1 , total vegetables is 121.90 g day −1 , green FV is 65.11 g day −1 , red/purple FV is 62.05 g day −1 , orange/ yellow FV is 48.62 g day −1 , white FV is 100.97 g day −1 , and uncategorized is FV 28.17 g day −1 .…”
Section: Food and Function Papermentioning
confidence: 99%
“…The present report aims to highlight the importance of understanding the interaction (both beneficial and detrimental) between herbal supplements and cytotoxic medicines. In vivo mouse experiments have shown the activity of elderberry in breast, bladder and ovarian cancer ( 24 ). It is thought that elderberry flower exerts its medicinal effect due to the abundance of polyphenolic compounds contained in it, primarily flavonols, phenolic acid and anthocyanins.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, pectins, tannins, and phenolic acids have also been found in elderflowers [ 23 , 26 ]. Elderflowers can be used both for the prevention and therapy of a wide array of diseases due to their immunomodulatory, anti-inflammatory, antimicrobial, antioxidant, and antiviral activities [ 27 , 28 ].…”
Section: Introductionmentioning
confidence: 99%